Lingustic Stereotype toward Osakan Dialect Speaker in Fiction - Hardianto Rahardjo (WIDAI Japanese Journal, 2020)
Linguistic Stereotype is an image that closely related to certain speakers of certain style of speaking, language and dialects or accents. This type of stereotype usualy derived from the image where the language or accents came from. In Japanese fictions and stories such as anime and manga, the fictional characters often depicted as possessing characteristics and habits suitable to the stereotypes their speaking style and dialects cary. This article is written to describes and analyze the example of said phenomenon, in which Osakan dialect fictional speakers are often depicted with unique characteristics in accordance with the dialect they spoke with. This gaves an iamge to non-native readers that the majority of Osakan people in real world Japan are really act and be the way they are depicted in the fiction.